High yielding synthesis of 2, 2′-bipyridine macrocycles, versatile intermediates in the synthesis of rotaxanes. Issue 5 (8th February 2016) - Lewis, J. E. M.; Bordoli, R. J.; Denis, M.; Fletcher, C. J.; Galli, M.; Neal, E. A.; Rochette, E. M.; Goldup, S. M.
Abstract : We present a simple approach to bipyridine macrocycles in remarkable yields (typically >65%) and demonstrate their application in efficient rotaxane synthesis. Abstract : We present an operationally simple approach to 2, 2′-bipyridine macrocycles. Our method uses simple starting materials to produce these previously hard to access rotaxane precursors in remarkable yields (typically >65%) across a range of scales (0.1–5 mmol). All of the macrocycles reported are efficiently converted (>90%) to rotaxanes under AT-CuAAC conditions. With the requisite macrocycles finally available in sufficient quantities, we further demonstrate their long term utility through the first gram-scale synthesis of an AT-CuAAC [2]rotaxane and extend this powerful methodology to produce novel Sauvage-type molecular shuttles.